PARTISIPASI KOMITE AUDIT DAN KOMITE MANAJEMEN RISIKO SELAKU ORGAN DEWAN KOMISARIS TERHADAP KINERJA KEUANGAN PERUSAHAAN ASURANSI DAN REASURANSI DI INDONESIA - Ivana Pudiwan; Sekar Mayangsari (Media Riset Akuntansi, Auditing & Informasi, 2010)
The purposes of study are to examine the influences of Audit Committee and Risk Management Committee on financial performance of Insuranse and Reinsurance Company; and to drive a conclusion which is Audit Committee and Risk Management Committee applied to improve company's financial performance. In this research, Audit Committee and Risk Management Committee as independent variable which indicated by Audit Committee's member and Risk Management Committees member. Financial performance oflnsurance and Reinsurance Company as dependent variable is represented byfinancial ratio oflnsurance and Reinsurance Company also leverage and company measurement as control variable. Researcher using 25 insurance and reinsurance companies which are based on defined criteria, with research timeframe from the year of 2006 to 2008. The result of the research concluded that Audit Committee significantly influences financial performance of Insurance & Reinsurance Company and company measurement significantly influences financial performances of Insurance & Reinsurance Company. Risk Management Committee and leverage have not any influence on the financial performance of Insurance & Reinsurance Company. These facts indicate Audit Committee and company measurement could be applied in order to improve financial performance oflnsurance and Reinsurance Company.Keywords : Audit Committee, Risk Management Committee, Financial Performance